Peanut Variety Performance in Florida, 2010–2013 - Barry Tillman; Mark Gomillion; Justin McKinney; George Person (EDIS, 2014)
Variety choice is a critical management decision in producing a peanut crop. Since several good peanut varieties are available, it is essential to know each variety’s attributes and how different varieties might fit into a farm plan. This 7-page fact sheet provides data conducted from trials in Florida at UF/IFAS research centers located in Gainesville (Citra), Marianna, and Jay from 2010–2013. Written by Barry Tillman, Mark Gomillion, Justin McKinney, and George Person, and published by the UF Department of Agronomy, May 2014.